Waist circumference measurement sites and their association with visceral and subcutaneous fat and cardiometabolic abnormalities - Cláudia Porto Sabino Pinho (Archives of Endocrinology and Metabolism)
ABSTRACT Objectives: To estimate the degree of variability of the waist circumference (WC) when obtained in different anatomical sites and compare the performance of the measurement sites as predictors of visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) and cardiometabolic abnormalities. Subjects and methods: Cross-sectional study involving 119 individuals with overweight (50.3 ± 12.2 years), in which six WC measurement sites were evaluated (minimal waist, immediately below the lowest rib, midpoint between the lowest rib and the iliac crest, 2 cm above the umbilicus, immediately above the iliac crest, umbilicus level), in addition to the VAT and SAT (quantified by computed tomography) and cardiometabolic parameters. Results: The differences between the measurements ranged from 0.2 ± 2.7 cm to 6.9 ± 6.7 cm for men, and from 0.1 ± 3.7 cm to 10.1 ± 4.3 cm for women. The minimum waist showed significant correlation with VAT (r = 0.70) and with a higher number of cardiometabolic parameters among men. Regarding women, the WC measurement showed high correlation with SAT and moderate correlation with VAT, not being found superiority of one measurement protocol in relation to the others when assessed the correlation with VAT and with cardiometabolic parameters. Conclusions: Greater variability between the measuring sites was observed among women. With respect to men, the minimum waist performed better as a predictor of VAT and cardiometabolic alterations.